Perinatal factors among children with neurodevelopmental disorders attending tertiary care hospitals in Dhaka city - Zohra, Fatima; Alam, Md Faruq; Sarkar, Mekhala; Faruque, Shahriar; Hasnat Sajib, Mohammad Waliul (Bangladesh Journal of Psychiatry, 2020)
Neurodevelopmental disorders (NDD) are public health burden worldwide. NDD causes disabilities and reduces the quality of life. Perinatal factors like maternal age, stress, maternal physical illnesses, birth complications, preterm birth, low birth weight and neonatal infections are the important risk factors for NDD. The objectives of the study were to determine the proportion of perinatal factors among children with neurodevelopmental disorders attending tertiary care hospitals in Dhaka city. This was a cross-sectional study conducted in outpatient department of National Institute of Mental Health (NIMH), Dhaka and Institute of Paediatric Neurodisorder and Autism (IPNA), Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2017 to July 2018. Among 115 children with NDD aged 0-17 years satisfying inclusion and exclusion criteria who were conveniently selected as sample. After diagnosing NDD using DSM- 5 criteria by psychiatrists and paediatric neurologists, a semi structured questionnaire was applied by researcher herself that included socio-demographic and perinatal factors as well. Results showed that majority of the respondents (29.6%) were 5-8 years with male predominance (78.3%). The most common perinatal factors were maternal factors like maternal stress (68.7%), maternal physical illness (66.1 %), inadequate food/rest intake (53.9%) and inadequate weight gain during pregnancy (50.4%). Fetal and neonatal factors like birth complication (82.6%), preterm birth (80%), low birth weight (75.6%), neonatal illness (69.6%) and birth asphyxia (61.7%). Most common neonatal illness were pneumonia (30.0 %) followed by neonatal Jaundice (20%). Early identification of possible perinatal factors and providing safe perinatal period can give a positive impact in prevention of NDD in children. Bang J Psychiatry 2018;32(2): 26-31